Microstructure and Physical Properties of Glycerol Doped by Oxidized Multiwalled Carbon Nanotubes - I. A. Melnyk; L. A. Bulavin; S. V. Hrapatyi; G. I. Dovbeshko; E. A. Solovyova; V. A. Mykhailyk; N. I. Lebovka (Хімія, фізика та технологія поверхні)
The effect of acid treatment on the structure and properties of suspensions of multiwalled carbon nanotubes (MWCNTs) in glycerol has been investigated. The concentrations of MWCNTs were within 0–2% by weight. Suspensions were treated during 5–60 min at T = 343 K by a mixture of concentrated nitric and sulphuric acids with the volume ratio of 1:3. The degree of acid treatment influence on the structure of suspension was analyzed using methods of thermal analysis and infrared spectroscopy. Oxidation of MWCNTs could affect significantly their thermal stability and degree of destruction. The changes in the structure of MWCNT clusters in glycerol, electrical conductivity and percolation behaviour of the systems are discussed. The acid treatment is shown to cause significant decrease in conductivity of suspension and enhancement of its temperature dependence. Reduction of the length of MWCNTs after acid treatment is reported.